A Case Study of an Ignored Facet: Metacognitive Experiences - Nesrin Ozturk (e-Kafkas Eğitim Araştırmaları Dergisi)
Metacognitive experiences, a component of metacognition, may have distinctive characteristics at eachinstance, and they help relate and practice metacognitive knowledge and strategies. This case studyexamines pre-service teachers’ task-specific metacognitive experiences and strategic planningperformances. Data were collected from 187 volunteers via four different tasks with compatibledemands and the Metacognitive Experiences Questionnaire, delivered before and after taskcompletion. The reasons behind task selection were coded thematically, and performance scores werecoded regarding the complexity of strategic planning. Findings confirmed that strategic planningperformance did not vary across tasks, reasons, or class levels. Moreover, while the data did not fit thetheoretical model of the Metacognitive Experiences Questionnaire, an exploratory factor analysisproduced a three-factor solution for task-specific metacognitive experiences. Task-specificmetacognitive experiences in this study may be represented by metacognitive estimates, feelings, andjudgments, and they explained 59.5% of the variance. Post-task correctness and confidence judgmentswere significant predictors. While correctness judgments may facilitate performance, confidence mayimpose false adequacy judgments, implying the Dunning-Kruger effect.